Chant, Sylvia i McIlwaine, Cathy (2016). Cities, slums and gender in the Global South. Towards a feminised urban future - Ortiz Guitart, Anna (Documents d’Anàlisi Geogràfica, 2018)
Chant, Sylvia i McIlwaine, Cathy (2016) Cities, slums and gender in the Global South. Towards a feminised urban future Oxon: Routledge, 299 p. ISBN 978-0-415-72164-6